Mixed-member electoral systems in constitutional context : Taiwan, Japan, and beyond - Batto, Nathan F.; Cox, Gary W.; Huang, Chi; Tan, Alexander C. (2016)
After the electoral reform in 1994, Japan saw a gradual evolution from a multi-party system toward a two-party system over the course of five House of Representatives election cycles. In contrast, after Taiwan’s constitutional amendment in 2005, a two-party system emerged in the first post-reform legislative election in 2008. Critically, however, Taiwan’s president is directly elected while Japan’s prime minister is indirectly elected. The contributors conclude that the higher the payoffs of holding the executive office and the greater degree of cross-district coordination required to win it, the stronger the incentives for elites to form and stay in the major parties. In such a context, a country will move rapidly toward a two-party system. ...